Natural filters of marine microplastic pollution: implications for plants and submerged environments - Adaro, María Eugenia (2024)
Despite numerous studies assessing the effects of microplastics (MPs) on soils and plants and their potential implications for human consumption and agriculture, there remains a lack of exploration on the role of vegetated ecosystems as natural filters of MPs pollution. The MPs stemming from anthropogenic continental activities may undergo retention within these ecosystems, preventing their dispersion into aquatic environments. However,questions are raised about their potential impact on plant health and soil quality. This review aims to address these gaps by examining studies analyzing the role of vegetated ecosystems in MPs retention, the sources and effects of these contaminants on soils, and their absorption/translocation into plants analyzing their direct effects on plant physiology and growth. Finally, future perspectives and knowledge gaps in these crucial research areaswere explored. The main findings demonstrate that plants effectively play a crucial role in retaining MPs, with studies mainly focused on vegetated wetlands with halophytes, and that MPs could affect various soil properties, including bulk density, water retention, and microbiota, inducing oxidative stress on plants and disturbing their growth.However, research gaps persist, such as quantifying MPs in natural settings and investigating the complex relationship between MPs, plants, and ecosystems. Experiments often employed high concentrations of MPs, potentially deviating from natural environmental levels and thus requiring assessment of whether observed concentrations can elicit comparable effects. Additionally, the predominant focus on primary MPs in experiments overlooked other types derived from degradation of larger plastic items, warranting attention and inclusion in research efforts.In conclusion, vegetated ecosystems can naturally filter MPs from land-based activities before they reach aquatic environments. Nevertheless, these particles exhibit significant impacts on soil properties and plant growth, posing an emerging threat to terrestrial ecosystems that requires further study.